Major thrombotic complications with lower limb PICCs in surgical neonates - Kisa, Phyllis; Ting, Joseph; Callejas, Allison; Osiovich, Horacio; Butterworth, Sonia A. (Journal of Pediatric Surgery, 2015)
PICC lines are now used routinely to provide central access for neonatal intensive care unit (NICU) patients. Neonates are known to be at risk for venous thromboembolism (VTE) related to central catheters. No literature exists about VTE PICC-related morbidity in the NICU abdominal surgery subgroup.With REB approval, a retrospective review of a NICU database of PICC insertions performed at a tertiary children's hospital was conducted (January 2010–June 2013). Information about PICCs and complications was recorded. For patients with a major thrombotic complication, charts were reviewed. A major thrombotic complication was defined as a thrombosis which required medical and/or surgical intervention.692 PICCs were inserted (485 in the upper extremity, 142 in the lower extremity, and 65 in the scalp). Seventy-four patients had significant intraabdominal pathology, and 5 had a major thrombotic complication. All patients with a major thrombotic complication had a lower extremity PICC which was at or below L1 (L1-S1) running parenteral nutrition.In the current study, only neonates with abdominal pathology and a lower extremity insertion site suffered major thrombotic complications from PICC lines. Given all patients' PICC tips were below the recommended location, more rigorous surveillance (with repositioning if required) may avoid these complications for future patients.
Keywords: Venous thrombo-embolism; PICCs; Neonates; NICU; Abdominal surgery